Identification and characterization of the karrikins signaling gene SsSMAX1 in Sapium sebiferum - Ni, Fang; Shah, Faheem Afzal; Ren, Jie (PeerJ, 2023)
SUPPRESSOR OF MAX2 LIKE 1 (SMAX1) is a member of the SUPPRESSOR of MAX2 1‑LIKE family of genes and is known as a target protein of KARRIKIN INSENSITIVE2 (KAI2)-MORE AXILLARY BRANCHES2 (MAX2), which mediates karrikin signaling in Arabidopsis. SMAX1 plays a significant role in seed germination, hypocotyl elongation, and root hair development in Arabidopsis. SMAX1 has not yet been identified and characterized in woody plants. This study identified and characterized SsSMAX1 in Sapium sebiferum and found that SsSMAX1 was highly expressed in the seed, hypocotyl, and root tips of S. sebiferum. SsSMAX1 was functionally characterized by ectopic expression in Arabidopsis. SsSMAX1 overexpression lines of Arabidopsis showed significantly delayed seed germination and produced seedlings with longer hypocotyl and roots than wild-type and Atsmax1 functional mutants. SsSMAX1 overexpression lines of Arabidopsis also had broader and longer leaves and petioles than wild-type and Atsmax1, suggesting that SsSMAX1 is functionally conserved. This study characterizes the SMAX1 gene in a woody and commercially valuable bioenergy plant, Sapium sebiferum. The results of this study are beneficial to future research on the molecular biology of woody plants.
Keywords: SMAX1; Seed dormancy; Seedlings development; Hypocotyl length; Root length